Implementasi Nilai-nilai syariah Dalam Meningkatkan Kinerja Asuransi Syariah di Jawa Tengah - Koentjoro, Wuryanti (PRESTASI, 2012)
One cause of Takaful undeveloped is still a lack of public education about Islamic insurance and service quality, customer satisfaction and loyalty are still not optimal. The purpose of this study is to conduct in-depth study of consumer preferences on Islamic insurance products as well as respondents perceptions of service quality, wholesale price, satisfaction and consumer loyalty to sharia. The samples in this study were clients Takaful Insurance Semarang and Surakarta branch, Bumiputera Life Sharia Semarang, Bumida Life Sharia Semarang, Beringin Life Sharia Semarang, total of 140 respondents.. Data were collected through questionnaires and interviews. Data analysis was done by descriptive analysis and empirical testing using AMOS. The results showed that perceptions of service quality has positive and significant effect on satisfaction. Perceptions of prices have a positive and significant impact on satisfaction holders. Satisfaction has positive and significant effect on loyalty. Service quality has positive and significant effect on loyalty.Keyword: Takaful, price, service quality, customer satisfaction, loyalty